Optimization of Glycerolysis Temperature Process for the Synthesis of Monoglyceride-Diglyceride Surfactants Derived from oil of Silkworm Pupae - Ery Fatarina Purwaningtyas (Seminar Nasional Teknik Kimia Kejuangan, 2015)
The value-added of silkworm pupae could still be increased through conversion of the pupae into surfactants. Such animal-based surfactants are believed to have similar characteristics as those of plant-based surfactants, i.e. biodegradable and environmentally friendly. One of the animal-based surfactants that can be synthesized from oil of silkworm pupae is monoglyceride, through a glycerolysis using MgO as catalyst. The current research examined the possibility of synthesizing monoglyceride (MG )and diglycerides (DG) using silkworm pupae as raw materials through glcerolysis. The experiments were done using MgO as catalyst and n-butanol as the solvent, with varying temperatures.It was found that the most dominant variable was temperature, with the highest conversion of 0.7094. The column chromatograph demonstrated the highest yield of MG-DG as 7.96 g for the following: glycerol – oil ratio = 3; reaction time = 4 h; temp = 90oC, agitation rate = 400 rpm, and catalyst conc.= 2%. Fourieer Transformer Infra Red analysis showed the peak of 1041.56 cm-1 which corresponds to the functional group of C-OH and peak of 3659.61 cm-1 the functional group OH. The emulsion stability test proved that MG as surfactant had an emulsifying effect on a benzene-water system.